2019
DOI: 10.1186/s40249-019-0576-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the national programme on prevention of mother-to-child transmission of hepatitis B virus in China, 2016–2017

Abstract: Background In addition to providing free hepatitis B vaccine (HBvacc) series to all infants in China since 2005, the national programme on prevention of mother-to-child transmission (PMTCT) of hepatitis B virus (HBV) started providing free hepatitis B immunoglobulin for all new-borns born to hepatitis B surface-antigen (HBsAg) positive mothers in 2010. However, few studies have evaluated the effectiveness of the PMTCT programme. Therefore, we aimed to investigate the outcomes of the programme and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Like previous reports, our study also demonstrated that maternal high HBV DNA levels and hepatitis B e antigen (HBeAg) positivity were risk factors for MTCT . After ruling out all cases with antiviral, the MTCT rate among HBeAg‐positive mothers without amniocentesis was 2.14% (3/140) (Table S1), which was a relatively moderate transmission rate compared with recently reported 1.28% (2/156), 2.04% (3/147), 2.70% (33/1221), 3.20% (12/374), and 6.82% (6/88, with maternal HBV DNA > 2 × 10 6 IU/mL) . Meanwhile, the MTCT rate among HBeAg‐positive mothers underwent amniocentesis was 11.11% (4/36) (Table S1), which was obviously higher than above reported results.…”
supporting
confidence: 81%
“…Like previous reports, our study also demonstrated that maternal high HBV DNA levels and hepatitis B e antigen (HBeAg) positivity were risk factors for MTCT . After ruling out all cases with antiviral, the MTCT rate among HBeAg‐positive mothers without amniocentesis was 2.14% (3/140) (Table S1), which was a relatively moderate transmission rate compared with recently reported 1.28% (2/156), 2.04% (3/147), 2.70% (33/1221), 3.20% (12/374), and 6.82% (6/88, with maternal HBV DNA > 2 × 10 6 IU/mL) . Meanwhile, the MTCT rate among HBeAg‐positive mothers underwent amniocentesis was 11.11% (4/36) (Table S1), which was obviously higher than above reported results.…”
supporting
confidence: 81%
“…We used data from the Management Information System of the National Integrated Prevention of Mother-to-Child Transmission of HIV, Syphilis and Hepatitis B Programme (iPMTCT Programme) from 2015 to 2020 in mainland China. The National iPMTCT Programme, funded by the Government of China, was started in 2011 in 1156 (41%) county-level administrative units (briefly, counties) and expanded to all the 2856 counties nationwide by 2015 [ 16 , 17 ]. All the health-care facilities providing midwifery and antenatal care services were required to participated in the programme [18] .…”
Section: Methodsmentioning
confidence: 99%
“…8 There are 16-18 million mothers giving birth each year in China, nearly 6% of whom have chronic HBV infections, and onethird of them having a high HBV load. 9,10 One to 9% of infants born to HBV-carrying mothers may be infected with HBV, despite receiving HBIG plus HBV vaccine in the immediate neonatal period. 11 Furthermore, the risk of developing chronic HBV infection is strongly associated with the age of exposure.…”
Section: Introductionmentioning
confidence: 99%